Cytotoxic action of Brazilian propolis in vitro on canine osteosarcoma cells - Cinegaglia, N. C. [UNESP]; Bersano, P. R O [UNESP]; Búfalo, M. C. [UNESP]; Sforcin, José Mauricio [UNESP] (Wiley, 2013)
Osteosarcoma (OSA) is a primary bone neoplasm frequently diagnosed in dogs. The biology of OSA in pet dogs is identical to that of pediatric patients, and it has been considered an excellent model in vivo to study human OSA. Since the individual response to chemotherapy is unpredictable and considering that propolis is a natural product with several biological properties, this work evaluated the cytotoxic action of propolis on canine OSA cells. The primary cell culture of canine OSA was obtained from the tumor of a dog with OSA. Cell viability was assessed after incubation with propolis, 70% ethanol (propolis solvent), and carboplatin after 6, 24, 48, and 72 h. Cell viability was analyzed by the crystal violet method. Data showed that canine OSA cells were sensitive to propolis in a dose- and time-dependent manner and had a distinct morphology compared to control. Its solvent (70% ethanol) had no effect on cell viability, suggesting that the cytotoxic action was exclusively due to propolis. Our propolis sample exerted a cytotoxic effect on canine OSA cells, and its introduction as a possible therapeutic agent in vivo could be investigated, providing a new contribution to OSA treatment. Copyright © 2012 John Wiley & Sons, Ltd.
Keywords: chemotherapeutic agents; osteosarcoma; propolis